Efek Color Retention Agent pada Mi Basah dengan Pewarna Alami Cabai Merah (Capsicum Annuum L.) pada Karakteristik Fisikokimia - Alyarahma Nur Aisya; Siti Susanti; Bhakti Etza Setiani (Institut Pertanian Bogor, 2021)
There are many innovations in wet noodle processing with color variations. One of wet noodle processing innovations is the use of natural dyes such as fruit or vegetable dyes. The essence of red chilies can be used as a natural dye for wet noodles. Natural dyes dissolve easily during the boiling process, therefore color retention agents can be added in the processing and expected to be able to retain the red color of chilies in wet noodles. This study aims to determine the effect of adding color retention agents on physicochemical characteristics, namely moisture content, color resistance, texture, and vitamin C content in wet noodles. The method used in this study was a completely randomized design (CRD) with 5 treatments of color retention agents each with 4 repetitions. The treatments applied were T0: without the addition of a color retention agent, T1: ascorbic acid (C6H8O6), T2: citric acid (C6H8O7), T3: magnesium hydroxide (Mg(OH2)), and T4: magnesium carbonate (MgCO3). The test results were analyzed using Analysis of Variance (ANOVA) and if there is a significant effect at the 5% significance level, then proceed with the Duncan Multiple Region Test to determine the differences between treatments. All data analyses were calculated by using a computer program SPSS 21.0 for windows. Data from the test for vitamin C content were analyzed using Microsoft Excel through graphical analysis. The results is addition of color retention agent treatment to wet noodles with natural dyes from chilies had a significant effect on the color resistance, moisture content, texture, and vitamin C content of wet noodles. T4 wet noodle is the best wet noodle treatment in maintaining the red color with the physical characteristics according to SNI. Keywords: color retention agents, noodles, red chili